PENGARUH METODE READING ALOUD TERHADAP KEMAMPUAN MEMBACA DAN MINAT BACA SISWA KELAS III UPTD SDN 1 KEDOKANBUNDER - Tobroni; Piyantina Rukmini; Inayatus Sholihah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by students' low reading ability and interest in Indonesian language learning. The objective was to determine the effect of the read-aloud method on the reading ability and interest of third-grade students at the UPTD SDN 1 Kedokanbunder. This study used an experimental method with a pretest-posttest control group design. The sample was randomly selected: class III A as the experimental class and class III B as the control class, each consisting of 30 students. Data were collected through a reading test and a reading interest questionnaire, then analyzed using an independent sample t-test. The results showed that the read-aloud method significantly improved reading ability (sig. = 0.000 < 0.05), but had little effect on students' reading interest (sig. = 0.934 > 0.05). Thus, the read-aloud method is effective in improving reading ability, but not sufficient to increase students' reading interest.